Implementation of a Domestic Power Line Quality Measurement System - Prashanth, K.; Thiruvaran, T.; Nishanth, A.; Vinothine, S. (IEEE, 2017)
Electricity has become a vital commodity in the contemporary world. People use electricity to fulfill most of their day-to-day needs. For a better electricity supply network, two parameters should be satisfied namely, reliability and power quality. After fulfilling the reliability criteria of the electricity network, the consumer will expect a regulated and cost effective supply of power. Therefore, monitoring and analyzing the quality of the power supply becomes a major requirement. However, electricity service providers do not always disclose the power quality to consumers, particularly in developing countries. Moreover, in some places the service providers do not even measure the quality. Thus, it is left to the consumers to measure the power quality if there is a concern about it. This paper discusses implementation of a simple power quality analyzer which includes data collection, storage and power quality analyzer. Different quality parameters which are used to describe a power supply have been taken into the analysis.
Keywords: Power quality; Data collection